Immobilization of Interfacial Activated Candida rugosa Lipase Onto Magnetic Chitosan Using Dialdehyde Cellulose as Cross-Linking Agent - Wang, Shushu; Li, Shan; Liu, Runtang; Zhang, Wei; Xu, Huajin; Hu, Yi (Frontiers in Bioengineering and Biotechnology, 2022)
Candida rugosa lipase (CRL) was activated with surfactants and covalently immobilized onto a nanocomposite (Fe3O4-CS-DAC) fabricated by combining magnetic nanoparticles Fe3O4 with chitosan using polysaccharide macromolecule dialdehyde cellulose (DAC) as the cross-linking agent. Fourier transform infrared spectroscopy, transmission electron microscope, thermogravimetric analysis and X-ray diffraction characterizations confirmed that the organic-inorganic nanocomposite support modified by DAC was successfully prepared. Enzymology experiments confirmed that high enzyme loading (60.9 mg/g). The stability and reusability of immobilized CRL (Fe3O4-CS-DAC-SDS-CRL) were significantly improved simultaneously. Circular dichroism analysis revealed that the active conformation of immobilized CRL was maintained well. Results demonstrated that the inorganic-organic nanocomposite modified by carbohydrate polymer derivatives could be used as an ideal support for enzyme immobilization.